Organizations in industry - Carroll, Glenn R. (Oxford University Press, 1995)
Organizations in Industry offers an in-depth look at historical organizational reality. Intended as a real world companion to classes that involve the theoretical analysis of formal organizations, this straightforward, accessible text presents an inside look at the actual structure and evolution of numerous different industries. Individual chapters are on specific industries and discuss developments from the origin of the industry to the near present, covering automobile manufacture, biotechnology, financial services, health care, labor organizing, microcomputer manufacture, art museums, newspaper publishing, radio broadcasting, railroad transport, and telephony. Ideal for any course in organizational behavior or theory, the benefits of this approach include practical institutional knowledge about particular industries, valuable insight into organizational society through comparative analysis, a clear understanding of the real-life difficulty associated with organizational change, and an opportunity to study the operation of selection processes among organizations